Analisis Hukum Pidana terhadap Praktik Jual-Beli Rekening Bank dalam Transaksi Judi Online di Indonesia - Milen, Swity; Nasution, Rasina Padeni (IAIN Langsa, 2025)
The advancement of technology has triggered the emergence of various new crime modes, including online gambling, which utilizes bank accounts as a means of financial transactions. These accounts are often obtained through syndicates that purchase them from the public at high prices. This practice raises legal issues as there are no specific regulations governing the buying and selling of bank accounts for online gambling transactions. This study aims to analyze the legal framework for online gambling transactions in Indonesia, examine the criminal law perspective on the trade of bank accounts for such transactions, and assess the forms of criminal liability for the perpetrators. The research employs a normative juridical approach with conceptual and legislative analyses. The findings indicate that, to date, there are no specific regulations governing the trade of bank accounts or online gambling in Indonesia, despite both being illegal activities. Consequently, criminal liability for those involved in selling bank accounts cannot be firmly enforced due to the absence of clear legal provisions. Therefore, regulatory reforms are necessary to accommodate the evolving nature of technology-based crimes.